Sinergitas Guru dalam Mengatasi Perilaku Indisipliner Siswa di MAN 1 Ponorogo - Wilis Werdiningsih; Binti Ahlaku Mukaromah (Fakultas Tarbiyah dan Ilmu Keguruan UIN Kiai Ageng Muhammad Besari Ponorogo, 2024)
The purpose of education cannot be separated from the role of a teacher, namely educating, guiding, teaching and training. With synergy between moral belief teachers and guidance and counseling teachers, students can overcome disciplinary behavior. The moral aqidah teacher has the role of providing an understanding of religious values, while the guidance and counseling teacher has the role of providing guidance and counseling services to students. This research aims to analyze the synergy of the moral aqidah teacher and guidance teacher in overcoming student disciplinary behavior at MAN 1 Ponorogo. Data collection was carried out using interviews, observation and documentation techniques. With the data analysis stage using the interactive model analysis technique of Milles, Huberman, and Saldana. Meanwhile, the technique for checking the validity of the data in this study uses triangulation techniques. Based on data analysis, it was found that the synergy between moral aqidah teachers and guidance and counseling teachers was well established, while the form of synergy that existed was establishing communication, coordination and cooperation in developing their respective roles to complement each other. Supporting factors come from the teacher and family environment while inhibiting factors come from the student's personality and friendship environment. With the role of moral belief teachers and guidance and counseling teachers, they can help overcome disciplinary behavior even though it is not yet completely perfect. Because there needs to be role and support from all teachers, staff, and employees at the Madrasah.